Early-Onset Benign Occipital Seizure Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The recognition of a syndrome of early-onset benign childhood occipital seizures (EBOS) is proposed in a report from St Thomas' Hospital. London, England.